ANALISIS PERILAKU ISOTERM, TERMODINAMIKA, DAN KINETIKA ADSORPSI STRONTIUM MENGGUNAKAN TiO2 – ZEOLIT LAMPUNG - Sholahudin, M. Fiqri; Purwaningsih, Henny; Noerpitasari, Erlina; Boybul, Boybul; Yanlinastuti, Yanlinastuti (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
After being used in the reactor, nuclear fuel produces several fission products, one of which is strontium (90Sr). Strontium isotopes can be used as raw material for making batteries, but the strontium is still mixed with fission products or other isotope so a separation process is needed. One method of separating strontium is by adsorption. In this research, the Lampung TiO2-zeolite mixture was evaluated for its performance as an adsorbent so that it can be used for strontium adsorption. Lampung Zeolite was initially activated using concentrated sulfuric acid to clean pores that still contained impurities. Then the zeolite is mixed with TiO2 using the stir casting method. The Lampung TiO2-zeolite adsorbent obtained was then characterized using Fourier Transform Infrared (FTIR), X-Ray Diffraction Spectrometer (XRD), and Scanning Electron Microscope (SEM). After that, adsorption tests were carried out using isotherm, thermodynamic and kinetic models. The formation of TiO2-zeolite which was characterized using FTIR spectroscopy was shown by the presence of a Ti-O-Si absorption peak in the Lampung zeolite after TiO2 was added. The results of analysis using XRD show that the Lampung zeolite is clinoptilolite and mordenite, and the TiO2 used has an anatase phase. The results of analysis using SEM indicate that TiO2 is distributed on the surface of the Lampung zeolite. The adsorption isotherm model for the TiO2-zeolite adsorbent fulfills the Langmuir isotherm model. Thermodynamic studies show that the adsorption process is endothermic and not spontaneous, and the kinetics of strontium adsorption follows pseudo second order.